Model 3D Sebaran Lindi pada Lapisan Tanah di Area TPA Batulayang Pontianak Berdasarkan Nilai Resistivitas - Muhardi Muhardi; Muliadi Muliadi; Zulfian Zulfian (Jurnal Fisika FLUX, 2020)
The Final Disposal Site (TPA) of Batulayang Pontianak, West Kalimantan, uses an open dumping system so that it produces waste water (leachate). Its area on peatlands creates problems, especially in the distribution of leachate. The purpose of this study was to create a 3D model of leachate distribution in the soil layer in the TPA area of Pontianak Batulayang, West Kalimantan, based on the distribution of resistivity values. This study using the geoelectric resistivity method by the Wenner-Schlumberger configuration. The tracks that have been used are six, having a length of 117 m each. The results showed that the soil layer contaminated by leachate spreads from a depth of 5 m to 23.6 m. This layer is interpreted as sandy clay and sand, having a resistivity value of 0.152 Ωm to 13 Ωm. The results also showed that leachate comes from the West, North, and South directions, which spread to all study areas.